2022
DOI: 10.3389/fpls.2021.799482
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Sorghum [Sorghum Bicolor (L.) Moench] Accessions as Revealed by Single Nucleotide Polymorphism Markers

Abstract: Ethiopia is the center of origin for sorghum [Sorghum bicolor (L.) Moench], where the distinct agro-ecological zones significantly contributed to the genetic diversity of the crops. A large number of sorghum landrace accessions have been conserved ex situ. Molecular characterization of this diverse germplasm can contribute to its efficient conservation and utilization in the breeding programs. This study aimed to investigate the genetic diversity of Ethiopian sorghum using gene-based single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 80 publications
4
19
0
Order By: Relevance
“…According to the result of site-frequency spectrum analysis, there is substantial genetic diversity among the seven finger millet populations, as evidenced by variation in minor allele frequency distributions between them. However, individual accessions in different populations generally bear minor alleles at fewer loci compared to results obtained in a similar study in sorghum ( Enyew et al, 2021 ). More than 50% of individuals in Pop-5 and over 20% of individuals in Pop-6 had minor alleles in at least 10% of the SNP loci, as opposed to the other populations with minor alleles in less than 8% of the loci.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…According to the result of site-frequency spectrum analysis, there is substantial genetic diversity among the seven finger millet populations, as evidenced by variation in minor allele frequency distributions between them. However, individual accessions in different populations generally bear minor alleles at fewer loci compared to results obtained in a similar study in sorghum ( Enyew et al, 2021 ). More than 50% of individuals in Pop-5 and over 20% of individuals in Pop-6 had minor alleles in at least 10% of the SNP loci, as opposed to the other populations with minor alleles in less than 8% of the loci.…”
Section: Discussionmentioning
confidence: 55%
“…In line with the expectation, the mean He value (0.28) was higher than the mean Ho value (0.10) in the present study. A recent study in sorghum (a self-pollinating cereal crop) using 3001 SNP markers reported mean He and Ho values of 0.10 and 0.06 ( Enyew et al, 2021 ). The lower values in the latter case are most likely because most of the SNP markers used were located within genes ( Enyew et al, 2021 ) and hence are expected to be less diverse than GBS-based SNP markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorghum (Sorghum bicolor L.) is the fth most important crop in the world; it originated in Africa and is the most widely utilized C4 model crop [27][28][29]. In addition, sorghum is one of the most important food crops worldwide, especially in developing countries and areas with more drought and salinity [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Such variations range from single nucleotides to large-scale structural variations. However, most studies in the past have only used single nucleotide variations (Afolayan et al ., 2019; Enyew et al ., 2022) ignoring other structural variations such as insertion-deletions (indels) and presence-absence variations (PAV) (Saxena et al ., 2014). PAVs are present in some individuals but absent in others, making them perfect for detecting major differences among multiple genomes.…”
Section: Introductionmentioning
confidence: 99%